Overview of the 2022 WHO Classification of Familial Endocrine Tumor Syndromes - Nosé, Vania; Gill, Anthony; Teijeiro, José Manuel Cameselle; Perren, Aurel; Erickson, Lori (Endocrine pathology, 2022)
This review of the familial tumor syndromes involving the endocrine organs is focused on discussing the main updates on the upcoming fifth edition of the WHO Classification of Endocrine and Neuroendocrine Tumors. This review emphasizes updates on histopathological and molecular genetics aspects of the most important syndromes involving the endocrine organs. We describe the newly defined Familial Cancer Syndromes as MAFA-related, MEN4, and MEN5 as well as the newly reported pathological findings in DICER1 syndrome. We also describe the updates done at the new WHO on the syndromic and non-syndromic familial thyroid diseases. We emphasize the problem of diagnostic criteria, mention the new genes that are possibly involved in this group, and at the same time, touching upon the role of some immunohistochemical studies that could support the diagnosis of some of these conditions. As pathologists play an important role in identifying tumors within a familial cancer syndrome, we highlight the most important clues for raising the suspicious of a syndrome. Finally, we highlight the challenges in defining these entities as well as determining their clinical outcome in comparison with sporadic tumors. Instead of the usual subject review, we present the highlights of the updates on familial cancer syndromes by answering select questions relevant to practicing pathologists.